Kepribadian Individu dan Kesiapan untuk Perubahan Organisasi - Sari, Leni; Mustika, Meiviana; Zaitul, Zaitul (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
Change is necessary for organizations that want to develop in a dynamic business environment. In the context of the creative industry, such as kebaya design, readiness for change is a key factor determining the success of adaptation to market dynamics and trend developments. This research examines the relationship between personality attitudes and readiness for change in kebaya designer organizations in Indonesia. Using a quantitative approach, this study involved 57 kebaya designers as respondents, who were determined through purposive sampling techniques. The results of the research show that personality dimensions, namely openness to experience, emotional stability and extroversion, have a positive effect on readiness for change. At the same time, the dimensions of agreeableness and conscientiousness do not affect readiness for change. This research provides deeper insight into the role of personality in readiness for change and practical insights for the development of change management strategies in the creative industry.